The Model of Insurance Companies Risk Based Capital - Djayadi, Haris; Adrianto, Henricus Judi; Arifian, Dini (International Journal of Economics and Financial Issues, 2018)
Purpose of this research is to find out effect of Investment, Premium Revenue, Claims, and Profit Company partially and together on Risk Based Capital of the loss insurance company. Population of this research are Insurance Companies registered in the Financial Services Authority and publish complete financial statements both on print media and corporate website period of 2013-2017 amounted 16 companies. Based on purposive sampling, there are 10 companies which fulfilled the sample requirements. The data used is the annual financial statements (audited). This research uses panel data regression and hypothesis testing using Eviews 8 application. Based on this research result Investment has positive relation but not significant to Risk Based Capital while Premium Revenue, Claims, and Profit Company have insignificant negative relation to Risk Based Capital. Independent variables of Investment, Premium Revenue, Claims, and Profit Company are simultaneously unable to effect the dependent variable Risk Based Capital significantly. The ability of independent variables of Investment, Premium Revenue, Claims, and Profit Company to explaining the dependent variable Risk Based Capital as parameter is 10.9%, while the rest equal 89.1% explained by other causes outside research model. Keywords: Investment, Premium Revenue, Claims, Profit Company, and Risk Based Capital JEL Classifications: G12, G22, G31 DOI: https://doi.org/10.32479/ijefi.7164